ASPECTS OF FORMING A TOURIST DESTINATION POSITIONING STRATEGY (Development Service Industry Management, 2024)
The main goal of integration interactions in tourism is the systemic development of a tourist destination. The formation of competitive business strategies of integration interaction in the development of a destination should be aimed at increasing the tourist attractiveness of tourist entities and creating favorable conditions for the development of the tourist business, which is possible only with the support of regional authorities. The marketing approach expands the idea of a destination as a territory; it exists physically and mentally in the minds of actual and potential tourists. The work analyzes the main phases of building a tourist destination positioning strategy and the expected results for each phase. The competitiveness criteria of a tourist destination positioning strategy are studied. Global trends in the development of recreation are designed to create conditions for every citizen of the country to use their abilities in creating a social product through constant encouragement of owners and managers of enterprises and their employees to improve their physical, mental, spiritual, and intellectual qualities.Understanding the factors, parameters, and stages of strategic planning, considering the specifics of the tourism industry, is an essential competence necessary for managing a local tourist destination. When conceptual strategic planning, the most essential condition must be observed: the planning process must be considered by tourism enterprises' internal and external networks (clusters). The strategy's success is all the more likely that it has more allies and fewer opponents. However, it is crucial for the implementation of the strategy to take into account not only the interests of individual community groups but also their legitimacy, scale, and opportunities to carry out active activities both in support of the strategy and in its containment. In this context, the construction of an effective public-private dialogue is essential.
Keywords: destination; strategy; tourism; strategic planning; development of a tourist region